Clinical phenotype of adult‐onset liver disease in patients with variants in ABCB4, ABCB11, and ATP8B1. Issue 10 (27th July 2022) - Nayagam, Jeremy S.; Foskett, Pierre; Strautnieks, Sandra; Agarwal, Kosh; Miquel, Rosa; Joshi, Deepak; Thompson, Richard J.
Abstract: Variants in ATP8B1, ABCB11, and ABCB4 underlie the most prevalent forms of progressive familial intrahepatic cholestasis. We aim to describe variants in these genes in a cohort of patients with adult‐onset liver disease, and explore a genotype–phenotype correlation. Patients with onset of liver disease aged above 18 who underwent sequencing of cholestasis genes for clinical purposes over a 5‐year period were identified. Bioinformatic analysis of variants was performed. Liver histology was evaluated in patients with variants. Of the 356 patients tested, at least one variant was identified in 101 (28.4%): 46 ABCB4, 35 ABCB11, and 28 ATP8B1 . Patients with ABCB4 variants had chronic liver disease (71.7%) and pregnancy‐associated liver dysfunction (75%), with a younger age of onset in more severe genotypes ( p = 0.046). ABCB11 variants presented with pregnancy‐associated liver dysfunction (82.4%) and acute/episodic cholestasis (40%), with no association between age of onset and genotype severity. ATP8B1 variants were associated with chronic liver disease (75%); however, they were commonly seen in patients with an alternate etiology of liver disease and variants were of low predicted pathogenicity. In adults with suspected genetic cholestasis, variants in cholestasis genes were frequently identified and were likely to contribute to the development of liver disease, particularly ABCB4 and ABCB11 . Variants were often in heterozygous state, and they should no longer be considered recessive Mendelian traits. Sequencing cholestasis genes in selected patients with adult‐onset disease should be considered, with interpretation in close collaboration with histopathologists and geneticists. Abstract : Variants in cholestasis genes were found in patients with adult‐onset liver disease. ABCB4 variants are associated with chronic biliary disease, variants in ABCB11 are seen in patients with acute cholestasis, and the clinical significance of ATP8B1 variants is not clear.image